Managing enterprise social media to develop consumer trust - Tseng H.-T.; Shanmugam M.; Magalingam P.; Shahbazi S.; Featherman M.S. (Emerald Publishing, 2023)
article; customer satisfaction; drawing; electronic commerce; entrepreneurship; food; human; human experiment; physician; social media; structural equation modeling; trust